2021
DOI: 10.1371/journal.pone.0242754
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of words within phrases: Temporal evolution of color-adjectives and object-nouns during simple composition

Abstract: In language, stored semantic representations of lexical items combine into an infinitude of complex expressions. While the neuroscience of composition has begun to mature, we do not yet understand how the stored representations evolve and morph during composition. New decoding techniques allow us to crack open this very hard question: we can train a model to recognize a representation in one context or time-point and assess its accuracy in another. We combined the decoding approach with magnetoencephalography … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…For our study, we used the vectors acquired from the skip-gram algorithm, a neural network trained to predict the context for a given word. We chose vectors from Word2Vec because the existing studies show that word vector representations of stimuli can be decoded from brain-imaging data in adults [Ruan et al, 2016, Kivisaari et al, 2019, Sudre et al, 2012, Murphy et al, 2011, Foster et al, 2021, Honari-Jahromi et al, 2021.…”
Section: Word Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our study, we used the vectors acquired from the skip-gram algorithm, a neural network trained to predict the context for a given word. We chose vectors from Word2Vec because the existing studies show that word vector representations of stimuli can be decoded from brain-imaging data in adults [Ruan et al, 2016, Kivisaari et al, 2019, Sudre et al, 2012, Murphy et al, 2011, Foster et al, 2021, Honari-Jahromi et al, 2021.…”
Section: Word Vectorsmentioning
confidence: 99%
“…Previous studies conducted on brain-imaging data recorded from adults have shown success in decoding word semantics [Papadimitriou et al, 2018, Fyshe et al, 2019, Honari-Jahromi et al, 2021; we extend this idea to brain-imaging data recorded from infants. Specifically, we analyze the change in neural response patterns as the infants hear single words.…”
Section: Introductionmentioning
confidence: 96%
“…For these purposes, we leveraged the emerging multivariate pattern analysis (MVPA) approach (Grootswagers et al, 2017;King et al, 2018;. Originated from fMRI (Haxby et al, 2001), the recent application of MVPA in M/EEG research has not only advanced cognitive neuroscience research in sensory, motor, and other cognitive domains (Cichy et al, 2014;Dobs et al, 2019;Draschkow et al, 2018;, but also provided profound insights into the sentence processing literature (Fyshe, 2020;Gwilliams et al, 2022;Heikel et al, 2018;Honari-Jahromi et al, 2021;Sassenhagen and Fiebach, 2019). Briefly speaking, in the case of EEG, MVPA exploits algorithms trained on patterns of EEG signals across multiple scalp electrodes, so as to classify whether single trials belong to one of the two/more mental states (conditions).…”
Section: Introductionmentioning
confidence: 99%
“…If the context is not sufficient to provide information about the meaning of the adjective, a representation of a sense definition can improve the results. Honari-Jahromi, Chouinard, BlancoElorrieta, Pylkka¨nen, Fyshe (2021) focus their attention on the collocations with adjectives as well and use a decoding approach to address the general question of how combinatory contexts affect the neural representations of word meanings. Their combinatory contexts were all noun phrases comprised of a color adjective and an object-describing noun, such as 'blue cup.'…”
Section: Introductionmentioning
confidence: 99%